Yield potentials of improved rice varieties for increased lowland rice production within the mankran watershed in Ghana - Ulzen, O.O.; Buri, M.M.; Sekyi-Annan, E.; Devkota, Krishna Prasad; Dossou-Yovo, Elliott Ronald; Ayamba, Benedicta Essel; Adjei, Eric Owusu (Informa UK Limited, 2023)
Rice production in Ghana is limited by low varietal choices, which puts farmers at a disadvantage in meeting the market demand for consumers. The objectives of this study were to (i) assess the yield potentials of improved rice varieties developed by the Africa Rice Center (AfricaRice), and (ii) to allow farmers to select improved varieties of their choice based on growth and yield, as observed in the field, in order to ensure a high adoption rate, increase productivity and food security. Two seasons (i.e. 2020 major and 2020–2021 minor) field experiments were conducted at two lowland within the Mankran watershed in the Ashanti region of Ghana. The experiment comprised thirteen (13) improved varieties and two local checks and was conducted using recommended good agronomic practices. The key findings of the study showed that growth and yield parameters vary significantly between varieties across locations. The biplot analysis showed that varieties FARO 66, SAHEL 317, and Amankwatia are the best in the major season while WITA 9, GT 11, ARS-957-BGJ-171-15-D-B, NERICA L36, and AGRA were the best in the minor season at both locations. Farmers’ preference for the varieties was based not only on growth and yield but on resistance to lodging, pests, and diseases. In conclusion, the best performing varieties have demonstrated yield potential which is about 92% higher than the yield of the local checks and can be recommended for adoption by farmers. Future breeding programs on these varieties should include the most preferred attributes by farmers in this study.